HMGB1 interacts with human topoisomerase IIalpha and stimulates its catalytic activity - Stros, Michal; Bacíková, Alena; Polanská, Eva; Stokrová, Jitka; Strauss, François (Nucleic acids research, 2007)
DNA topoisomerase IIalpha (topo IIalpha) is an essential nuclear enzyme and its unique decatenation activity has been implicated in many aspects of chromosome dynamics such as chromosome replication and segregation during mitosis. Here we show that chromatin-associated protein HMGB1 (a member of the large family of HMG-box proteins with possible functions in DNA replication, transcription, recombination and DNA repair) promotes topo IIalpha-mediated catenation of circular DNA, relaxation of negatively supercoiled DNA and decatenation of kinetoplast DNA. HMGB1 interacts with topo IIalpha and this interaction, like the stimulation of the catalytic activity of the enzyme, requires both HMG-box domains of HMGB1. A mutant of HMGB1, which cannot change DNA topology stimulates DNA decatenation by topo IIalpha indistinguishably from the wild-type protein. Although HMGB1 stimulates ATP hydrolysis by topo IIalpha, the DNA cleavage is much more enhanced. The observed abilities of HMGB1 to interact with topo IIalpha and promote topo IIalpha binding to DNA suggest a mechanism by which HMGB1 stimulates the catalytic activity of the enzyme via enhancement of DNA cleavage.
Keywords: represorové proteiny; piperaziny; DNA, Kinetoplast; DNA-topoisomerasy typu II; antigeny nádorové; Diketopiperazines; kruhová DNA; DNA, Circular; superhelikální DNA; inhibitory enzymů; adenosintrifosfát; Rats; elektroforéza v agarovém gelu; lidé; Nucleic Acid Conformation; konformace nukleové kyseliny; Humans; HMGB1 Protein; diketopiperaziny; Animals; kinetoplastová DNA; Antigens, Neoplasm; DNA, Superhelical; DNA Topoisomerases, Type II; Catalysis; Enzyme Inhibitors; Adenosine Triphosphate; High Mobility Group Proteins; DNA-Binding Proteins; Repressor Proteins; zvířata; DNA; protein HMGB1; krysa rodu Rattus; proteiny s vysokou pohyblivostí; katalýza; Electrophoresis, Agar Gel; Piperazines; DNA vazebné proteiny